Structure of the Fixed Point of Condensing Set-Valued Maps - Zeinab Soltani (Mathematics Interdisciplinary Research, 2020)
In this paper, we present structure of the fixed point set results for condensing set-valued map. Also, we prove a generalization of the Krasnosel'skii-Perov connectedness principle to the case of condensing set-valued maps.